2020
DOI: 10.3390/polym13010092
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Electrochemical Performance of a Composite Polymer Electrolyte Based on PVA-K2CO3-SiO2 Composite

Abstract: Composite polymer electrolyte (CPE) based on polyvinyl alcohol (PVA) polymer, potassium carbonate (K2CO3) salt, and silica (SiO2) filler was investigated and optimized in this study for improved ionic conductivity and potential window for use in electrochemical devices. Various quantities of SiO2 in wt.% were incorporated into PVA-K2CO3 complex to prepare the CPEs. To study the effect of SiO2 on PVA-K2CO3 composites, the developed electrolytes were characterized for their chemical structure (FTIR), morphology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 81 publications
1
18
0
Order By: Relevance
“…In addition, it is reported that the formation of hydrogen bonds will significantly affect the chemical shift of related hydrogen on the molecule, and there may be low-field movement. The 1 H NMR spectra revealed the effect of H-bonds between PVA and the drug (Figure b). The alcohol hydrogens of PVA showed three characteristic peaks at δ 4.26, 4.50, and 4.68. , Compared with the reported hydrogen-bonded hydrogel, the three hydroxyl peaks of PVA formed a new broad peak at δ 4.0–4.8, and the HDO peak at δ 3.50 disappeared. In the sequence of LUT, QUE, and MYR, this new peak gradually shifts to the low field.…”
Section: Resultsmentioning
confidence: 70%
“…In addition, it is reported that the formation of hydrogen bonds will significantly affect the chemical shift of related hydrogen on the molecule, and there may be low-field movement. The 1 H NMR spectra revealed the effect of H-bonds between PVA and the drug (Figure b). The alcohol hydrogens of PVA showed three characteristic peaks at δ 4.26, 4.50, and 4.68. , Compared with the reported hydrogen-bonded hydrogel, the three hydroxyl peaks of PVA formed a new broad peak at δ 4.0–4.8, and the HDO peak at δ 3.50 disappeared. In the sequence of LUT, QUE, and MYR, this new peak gradually shifts to the low field.…”
Section: Resultsmentioning
confidence: 70%
“…Researchers have recently shown great interest in developing polymer electrolytes (PEs) with specific properties, such as high ionic conductivity at ambient temperature, biodegradability, excellent mechanical properties, and robust performance in lightweight and thin energy storage systems [ 1 ]. Gel polymer electrolytes (GPEs) are one focus of research, due to their broad potential window and high ionic conductivity (close to that of liquid electrolytes) [ 2 ]. However, the fragile mechanical properties, internal short circuits, and restricted operating temperature of GPEs limit their practical applications in batteries and supercapacitors [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…58 This is confirmed by a shift of the peak for the −O−H stretching mode of −COOH at 3250 cm −1 (Figure S2, SI). 59 The hydrogen bonds facilitate the dispersion of the fumed SiO 2 in a polymer matrix. 60,61 From Figure 1A, the SEM micrographs confirm the uniform distribution of SiO 2 in P-SiO 2 (10%) and P-SiO 2 (20%).…”
Section: ■ Results and Discussionmentioning
confidence: 99%